Combination of palbociclib with enzalutamide shows in vitro activity in RB proficient and androgen receptor positive triple negative breast cancer cells - Liu, Chun-Yu; Lau, Ka-Yi; Hsu, Chia-Chi; Chen, Ji-Lin; Lee, Chia-Han; Huang, Tzu-Ting; Chen, Yi-Ting; Huang, Chun-Teng; Lin, Po-Han; Tseng, Ling-Ming (PLOS ONE, 2017)
Objectives Triple negative breast cancer (TNBC) lacks specific drug targets and remains challenging. Palbociclib, a cyclin-dependent kinases 4 and 6 (CDK4/6) inhibitor is approved for metastatic estrogen receptor (ER)-positive and human epithermal growth factor 2 (HER2)-negative breast cancer. The nature of cell cycle inhibition by palbociclib suggests its potential in TNBC cells. Retinoblastoma (RB, a known substrate of CDK4/6) pathway deregulation is a frequent occurrence in TNBC and studies have revealed that pharmacological CDK4/6 inhibition induces a cooperative cytostatic effect with doxorubicin in RB-proficient TNBC models. In addition, recent studies reported that anti-androgen therapy shows preclinical efficacy in androgen-receptor (AR)-positive TNBC cells. Here we examined the effect of palbociclib in combination with an anti-androgen enzalutamide in TNBC cells. Method MDA-MB-453, BT-549, MDA-MB-231 and MDA-MB-468 TNBC cell lines were used for in vitro studies. Protein expressions were assessed by Western blot analysis. Cytostatic effect was examined by MTT assay. Cell cycle and apoptosis were examined by flow cytometry. Results Palbociclib showed inhibitory effect in RB-proficient TNBC cells, and enzalutamide inhibited cell viability in AR-positive TNBC cells. Enzalutamide treatment could enhance the palbociclib-induced cytostatic effect in AR-positive/RB-proficient TNBC cells. In addition, palbociclib-mediated G1 arrest in AR-positive/RB-proficient TNBC cells was attenuated by RB knockdown. Conclusion Our study provided a preclinical rationale in selecting patients who might have therapeutic benefit from combining CDK4/6 inhibitors with AR antagonists.